Conventionalism about what? Where Duhem and Poincaré part ways. (December 2015) - Ivanova, Milena
Abstract: This paper examines whether, and in what contexts, Duhem's and Poincaré's views can be regarded as conventionalist or structural realist. After analysing the three different contexts in which conventionalism is attributed to them—in the context of the aim of science, the underdetermination problem and the epistemological status of certain principles—I show that neither Duhem's nor Poincaré's arguments can be regarded as conventionalist. I argue that Duhem and Poincaré offer different solutions to the problem of theory choice, differ in their stances towards scientific knowledge and the status of scientific principles, making their epistemological claims substantially different. Highlights: Pierre Duhem's and Henri Poincaré's views on scientific knowledge are examined. Conventionalism does not capture their solutions to theory choice and rationality. Conventionalism does not fully describe their epistemology of science